Investigation On Mechanical Properties Of Concrete On Partially Replacement Of Cement With Rice Husk Ash And Steel Fiber With Coarse Aggregate (International Journal of Innovative Research in Engineering & Management, 2022)
Globally, the demand of sustainable  development is increased; the industry’s basic challenge is  to fully extract the advantages with diminished use of  Portland cement. This can be possible if we use blended  cement and recyclable material in concrete which not only  reduce cost of construction but also reduce pollution.An  experimental program was planned in which one lean  concrete mix which did not include any percentage of rice  husk ash and rubber fibres and fifteen different mixes with  different combinations of Rice Husk Ash and steel Fibres  were prepared. Cubes and cylinder specimens were casted  to obtain the different physical properties of sixteen  concrete mixes with 0%, 7.5%, 12.5%, 17.5% and 22.5%  of rice husk ash as to replace some part of cement and 0%,  3%, 6% and 9% of steel fibers as to replace some part of  natural coarse aggregates. The cube specimens, cylindrical  specimens and beam specimens will be tested after the  recommended curing time of curing period of 7 days and  28 days respectively.
Keywords: Steel Fibre; Rice Husk; Coarse Aggregate; Rubber Fibre; Concrete